Impact of conservation agriculture practices on soil physical properties and yield of rainfed maize - BUTTAR, TEJBIR SINGH; SHARMA, VIKAS; ARYA, VIVAK M.; BHARAT, RAJEEV (Journal of Soil and Water Conservation, 2023)
A field experiment was conducted during Kharif, 2017 and 2018 at Jammu to study the effect of different conservation agriculture practices on soil physical properties and yield of rainfed maize. The experiment was laid out in Randomized Block Design (RBD) with 10 treatments and 3 replications i.e. T1 : Conventional Tillage (CT), T2 : CT+ Mulching (CTm), T3 : CT + Intercropping with mash (CTi),T4 : Minimum Tillage (MT), T5 : MT + Mulching (MTm),T6 : MT + Intercropping with mash (MTi),T7 : MT + Residue - 30% (MTr), T8 : Zero Tillage (ZT), T9 : ZT + Mulching (ZTm) and T10: ZT + Residue - 30% (ZTr). The results showed that statistically non-significant differences were observed in soil physical properties i.e. dispersion ratio, suspension percentage, water stable aggregates, mean weight diameter, geometric mean weight diameter, aggregate size distribution, bulk density and maximum water holding capacity. Many researchers have reported a positive and significant effect of conservation agriculture practices on physical properties of soil over longer periods of adoption and little or no effect on soil physical properties over a short period of one or two years. However, in our study no significant differences were noted due to short period study of two years. During 2017, the highest grain yield was recorded in MTi (31.7 q/ha) and the lowest in CTi (26.9 q/ha). During 2018, the highest grain yield was obtained in CT (31.0 q/ha) and the lowest in ZT (24.5 q/ha).